Yayasan UMP receives 32,000 copies of books worth RM200,000 - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 11 March 2021 - Yayasan UMP received a donation of 32,000 copies of the Quran and Fardhu Ain (KAFA) training book worth RM200,000.00 in collaboration with SME Corporation Malaysia and Fateh Resources Holdings Sdn. Bhd. which is the sole distributor of KAFA religious books as well as the publications of Syarikat Fargoes Sdn. Bhd.